A viral-fusion-peptide-like molecular switch drives membrane insertion of botulinum neurotoxin A1 - Kwok-ho Lam (Nature Portfolio, 2018)
The translocation domain (HN) of Botulinum neurotoxins (BoNTs) mediates the delivery of the BoNT light chain (LC) into neuronal cytosol. Here the authors provide insights into HN membrane insertion by determining the crystal structure of BoNT/A1 HN at acidic pH, which reveals a molecular switch in HN, where buried α-helices are transformed into surface-exposed hydrophobic β-hairpins.